Evaluating the precision of ultrasound versus computed tomography-guided measurement of cricoid cartilage diameter for double-lumen tube selection in thoracic surgery: A randomised comparative study - Roshni M. Mathew; Shefali Gautam; Rajesh Raman; Anurag Rai; Vinod K. Srivastava; Manish K. Singh (Indian Journal of Anaesthesia)
Background and Aims: Precise airway management is vital in thoracic surgeries to ensure patient safety and optimal outcomes. Choosing the correct double-lumen tube (DLT) size is challenging, as it typically relies on height, gender and subjective experience. This study investigates using ultrasonography (USG) and computed tomography (CT) to measure cricoid cartilage diameter for objective DLT sizing. Methods: In a randomised study, 120 adult patients undergoing elective thoracic surgery were randomised to three groups: Group A (DLT size determined by USG), Group B (DLT size determined by CT) and Group C (DLT size determined by conventional methods based on height and gender). The primary outcome variable was the appropriateness of DLT size. Secondary outcome variables were the degree of lung collapse and sore throat. Student’s t-test and ꭓ2 test were used to analyse continuous and dichotomous variables, respectively. Results: DLT sizing based on cricoid cartilage diameter improved the accuracy, with inappropriate sizes found in 25% in the conventional group, 5% in the USG group and 2.5% in the CT group (P < 0.05). Lung collapse was better in the USG (excellent in 92.5%) and CT (95%) groups compared to the conventional group (70%) (P < 0.05). Moderate sore throat was higher in the conventional group (37.5%) compared to the USG (5%) and CT groups (7.5%). Conclusion: The study demonstrates that USG- and CT-guided measurements of cricoid cartilage diameter are reliable and effective methods for determining DLT size in thoracic surgery compared to conventional methods.